Web-scale Discovery Service Adoption in Canadian Academic Libraries - Wong, Sandra (Partnership, 2020)
This study presents an overview of web-scale discovery service adoption in Canadian academic libraries. Web-scale discovery services (WSDS) have been widely embraced in Canadian academic libraries. EBSCO Discovery Service (EDS) is the most adopted system for colleges and institutes while Primo Central from Ex Libris dominates the university market for web-scale discovery services. Bundling web-scale discovery services with library services platform (LSP) implementations are increasing in Canada. This study shows that Canadian academic libraries that have migrated from a traditional integrated library system (ILS) to an LSP have also opted for their LSP vendor’s corresponding web-scale discovery service. As more Canadian academic libraries implement an LSP bundled with a web-scale discovery service, there may come a time when web-scale discovery services are no longer separated from discussions on LSPs. The choices available for LSP and web-scale discovery services are shrinking due to vendor mergers and acquisitions in this area.